Quality of life and psychological and gastrointestinal symptoms after cholecystectomy: a population-based cohort study - Eivind Ness-Jensen; Kristian Hveem; Stian Lydersen; Arne Talseth; Tom-Harald Edna (BMJ Open Gastroenterology)
Objective The study aims to examine gastrointestinal symptoms, quality of life and the risk of psychological symptoms after cholecystectomy.Design This is a prospective population-based cohort study based on the Nord-Trøndelag Health Study (HUNT) Norway. HUNT is a repeated health survey of the county population and includes a wide range of health-related items. In the present study, all 3 HUNT surveys were included, performed between 1984 and 2008. Selected items were scores on quality of life, the Hospital Anxiety and Depression Scale (HADS) and selected gastrointestinal symptoms. Participants who underwent cholecystectomy for gallstone disease between 1 January 1990 and until 1 year before attending HUNT3 were compared with the remaining non-operated cohort. Associations between cholecystectomy and the postoperative scores and symptoms were assessed by multivariable regression models.Results Participants in HUNT1, HUNT2 and HUNT3 were 77 212 (89.4% of those invited), 65 237 (69.5%) and 50 807 (54.1%), respectively. In the study period, 931 participants were operated with cholecystectomy. Cholecystectomy was associated with an increased risk of diarrhoea and stomach pain postoperatively. In addition, cholecystectomy was associated with an increased risk of nausea postoperatively in men. We found no associations between cholecystectomy and quality of life, symptoms of anxiety and depression, constipation, heartburn, or acid regurgitation following surgery.Conclusions In this large population-based cohort study, cholecystectomy was associated with postoperative diarrhoea and stomach pain. Cholecystectomy for gallstone colic was associated with nausea in men. There were no associations between quality of life, symptoms of anxiety and depression, constipation, heartburn, or acid regurgitation.